The Relative Role of Safety and Productivity in Canadian Ergonomists’ Professional Practices - Theberge, Nancy; Neumann, W. Patrick (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2013)
Definitions of ergonomics reference its application to both productivity and well-being. Discussions in the ergonomics literature consider the correspondence between these goals in ergonomic practice and make the case for a robust conception that advances the twin agendas of safety and productivity, contrary to the dominant understanding that ergonomics is primarily concerned with safety. This article examines the professional practices as reported from a sample of 21 ergonomists from across Canada with a combined experience of 296 years. The analysis aims to understand the reported intersection of safety and productivity in the ergonomists’ work and the broader conditions that structure this negotiation. Results provide strong support for the view that ergonomics is primarily associated with safety. This is evident in the structural location of ergonomics within health and safety units of workplaces and in ergonomists’ reports that the main focus of their work is safety concerns. A minority of study participants indicated that they addressed productivity concerns in their work, either as secondary or primary outcomes of ergonomic applications. In either instance, efforts to highlight the contribution of ergonomics to production did not significantly disrupt the dominant safety-oriented perception of the field. Financial considerations were major determinants of whether recommendations were accepted and implemented. The argument for the more robust vision of ergonomics advanced within the profession reflects an effort to overcome the organizational divide between safety and productivity by stressing that, in effective ergonomics applications, safety and productivity are joined in the production process and ergonomists have a main role to play in advancing both agendas. The analysis provided here has identified significant challenges to the adoption of this position. An irony of the dominant understanding of ergonomics as oriented to safety is that this provides the main basis for its growing presence in workplaces but also limits its applications.